2017
DOI: 10.1007/s11229-017-1380-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional individuation, mechanistic implementation: the proper way of seeing the mechanistic view of concrete computation

Abstract: I examine a major objection to the mechanistic view of concrete computation, stemming from an apparent tension between the abstract nature of computational explanation and the tenets of the mechanistic framework: while computational explanation is medium-independent, the mechanistic framework insists on the importance of providing some degree of structural detail about the systems target of the explanation. I show that a common reply to the objection, i.e. that mechanistic explanation of computational systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…On the other end, we find more restrictive accounts, e.g., syntactic (Fodor 1975(Fodor , 1981 and mechanistic accounts (Piccinini 2015;Coelho Mollo 2018). On these accounts, computing systems are typically distinguished by a stance-independent function.…”
Section: Social Computationsmentioning
confidence: 78%
“…On the other end, we find more restrictive accounts, e.g., syntactic (Fodor 1975(Fodor , 1981 and mechanistic accounts (Piccinini 2015;Coelho Mollo 2018). On these accounts, computing systems are typically distinguished by a stance-independent function.…”
Section: Social Computationsmentioning
confidence: 78%
“…More recent defenses include (among others): Chalmers (2011); Chirimuuta (2014Chirimuuta ( , 2018; Coelho Mollo (2018); Gallistel and King (2011); Weiskopf (2011).…”
Section: Pac-manmentioning
confidence: 99%
“…Instead, medium-dependent details are taken to explain by decomposition of the phenomena. On the separate-hierarchies picture implementation can be considered to have a non-mechanistic explanatory role: it explains how the explanandum, as well as the computational hierarchy are implemented (see (Coelho Mollo, 2018)).…”
Section: The Relation Between the Computational And Implementational mentioning
confidence: 99%
“…Several authors have recently suggested that computational explanations are a species of mechanistic explanation (Kaplan, 2011;Kaplan and Craver, 2011;Piccinini and Craver, 2011;Milkowski, 2013;Piccinini, 2015;Boone and Piccinini, 2016;Coelho Mollo, 2018;Dewhurst, 2018). The focus of most of these accounts is the neurocognitive sciences, in which computational models and explanations are central to the scientific investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation